Konsep Uji Asumsi Klasik pada Regresi Linier Berganda - Sholihah, Siti Mar'atush; Aditiya, Nanda Yoga; Evani, Elsa Saphira; Maghfiroh, Siti (Jurnal Riset Akuntansi Soedirman, 2023)
Progress is in the era of the 4.0 era where there are quite a lot of statistical analysis software to choose from. One of them is SPSS software which has quite high statistical analysis capabilities as seen from the results showing ease and in calculations it is able to analyze the variables in the research. From this, the researcher will explain the concept of classical assumption testing in multiple linear regression. The research method used in this research is quantitative research, researchers are not directly involved in the field to collect data, and one form of qualitative research is library research. The classical assumption tests that must be passed in a study using multiple linear regression models include several tests that must be passed by researchers, including normality testing, multicollinearity testing, heteroscedasticity testing, and autocorrelation testing.